2016
DOI: 10.1016/j.sjpain.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into enlarging and reducing the size of mirror reflections of the hand on experimentally-induced cold-pressor pain in healthy human participants

Abstract: AbstractBackground and aimsMirror visual feedback may be a useful clinical tool for reducing pain. Research suggests that reducing the size of a non-painful reflected hand can alleviate complex regional pain syndrome in the affected hand that is out of view. In contrast, research on healthy humans exposed to experimentally induced pain suggests that reducing the appearance of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…() found that magnifying a mirror reflection of the hand reduced contact‐heat pain, whereas minifying the reflected hand increased pain. In contrast, Johnson and Gohil () used cold‐pressor pain and found no difference in pain measures when magnifying and minifying reflections of the hand.…”
Section: Introductionmentioning
confidence: 96%
“…() found that magnifying a mirror reflection of the hand reduced contact‐heat pain, whereas minifying the reflected hand increased pain. In contrast, Johnson and Gohil () used cold‐pressor pain and found no difference in pain measures when magnifying and minifying reflections of the hand.…”
Section: Introductionmentioning
confidence: 96%
“…(), there was a significant moderate effect in favour of a magnified reflection compared with a normal‐sized reflection (SMD = −0.34, 95% CI = −0.63, −0.05), and a small effect in favour of mirror VF using a normal‐sized reflection compared with a minified reflection (SMD = 0.18, 95% CI = 0.01, 0.37). There were no significant differences in the other seven comparisons (Osumi et al., ; Johnson and Gohil, ).…”
Section: Resultsmentioning
confidence: 75%
“…Studies included in our systematic review used a variety of VF protocols ranging from a session of 1 min to 1 h 9 5 days a week 9 6 weeks. Visually distorting the size of painful body parts is another component of optimal technique that has aroused interest, despite few available studies on which to judge efficacy (Wittkopf and Johnson, 2016). Likewise, embodiment of the viewed body part, which describes the subjective experience of having a sense of one's own body, including a sense of ownership of body parts (Longo et al, 2008;de Vignemont, 2011), is considered an important determinant of outcome but rarely assessed in trials (McCabe, 2011;Foell et al, 2014;Wittkopf et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators have suggested that magnifying the body part increased anticipatory reactions associated with expectancies about the intensity of the experimentally-induced noxious stimuli and that this prepares individuals for exposure to the noxious event [12,13]. However, a study from our laboratory failed to detect differences in coldpressor pain by reducing and enlarging the appearance of the size of a hand using mirror visual feedback in 20 healthy human participants [14]. Furthermore, Osumi et al [15] found that on healthy participants with low thresholds to experimental pain reported unpleasant emotions towards a magnified hand and that two-point discrimination threshold decreased when the hand was magnified in participants with higher pain threshold.…”
Section: Distorting the Size Of Painful Body Parts Modulates Painmentioning
confidence: 93%